Durable super-hydrophilic coating for flexible substrate and preparation method of durable super-hydrophilic coating
By using durable superhydrophilic coatings prepared by materials such as aqueous copolyester emulsions containing hydroxyl and carboxyl group pendant groups, the problems of complex hydrophilic coating stability and preparation process in the prior art are solved, and excellent performance and durability on flexible substrates are achieved.
Patent Information
- Application Number
- CN202411940175.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
AI Technical Summary
The existing hydrophilic coatings have shortcomings in stability and preparation processes, especially in applications on flexible substrates, which are prone to wear and functional failure problems.
The durable superhydrophilic coating is prepared by using aqueous copolyester emulsions containing hydroxyl and carboxyl pendant groups, aqueous resin system curing agents, isopropanol and nanobarium sulfate and other materials. Through high-speed stirring, electrostatic treatment and curing treatment, a coating with excellent adhesion and flexibility is formed.
A coating with excellent durability, ultra-hydrophilicity and high light transmittance is achieved on a flexible substrate, avoiding functional degradation of the traditional coating under friction and aging conditions.
Smart Images

Figure CN119684879A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a coating and a method for preparing the same. Background Art
[0002] The hydrophilic coatings reported so far mainly include hydrophilic coatings based on silica, hydrophilic coatings based on the photocatalytic effect of titanium dioxide, and hydrophilic surface coatings based on coating surfactants or water-soluble polymers. The single-component titanium dioxide hydrophilic coating no longer exhibits hydrophilicity after the ultraviolet light is removed. The hydrophilic surface coating coated with a surfactant is easy to lose its surfactant and is not resistant to wiping and solvents. The organic polymer hydrophilic coating swells in water and has poor hardness and wear resistance. The silica hydrophilic coating has significant hydrophilic properties, but the insufficient mechanical strength of the coating is a key factor limiting its practical application. It is prone to wear during use, especially in an environment with greater friction, which will cause its function to gradually fail and its flexibility is poor. In addition, the preparation process of the silica hydrophilic coating is often more complicated, requiring precise control of multiple parameters, and the preparation method even involves cumbersome steps such as high-temperature heat treatment and etching, which increases the difficulty and cost of molding.
[0003] By constructing a rough structure on the surface of the hydrophilic organic coating and combining it with the high hardness and abrasiveness imparted by the inorganic components, the prepared organic-inorganic composite coating exhibits excellent super hydrophilicity and stability. However, the affinity and compatibility issues between the two phases still need further exploration and improvement. Summary of the invention
[0004] The present invention aims to solve the problems of poor stability and complicated preparation process of existing hydrophilic coatings, and further provides a durable super hydrophilic coating for a flexible substrate and a preparation method thereof.
[0005] A durable super hydrophilic coating for a flexible substrate is prepared by 100 parts by mass of an aqueous copolyester emulsion containing hydroxyl and carboxyl side groups, 2 to 35 parts by mass of an aqueous resin system curing agent, 5 to 30 parts by mass of isopropanol and 2 to 5 parts by mass of nano barium sulfate.
[0006] A method for preparing a durable super-hydrophilic coating for a flexible substrate is carried out according to the following steps:
[0007] 1. Preparation of aqueous emulsion:
[0008] Weigh 100 parts by mass of an aqueous copolyester emulsion containing hydroxyl and carboxyl side groups, 2 to 35 parts by mass of an aqueous resin system curing agent, 5 to 30 parts by mass of isopropanol and 2 to 5 parts by mass of nano-barium sulfate, and then stir at high speed until the mixture is uniformly mixed to obtain an aqueous emulsion;
[0009] 2. Coating:
[0010] The aqueous emulsion is coated on a substrate at a temperature of 40°C to 80°C, and finally dried to obtain a coating layer;
[0011] 3. Electrostatic treatment:
[0012] Performing electrostatic surface treatment on the coating layer by using a corona roller to obtain an electrostatically treated coating;
[0013] 4. Curing treatment:
[0014] The coating after electrostatic treatment is cured for 20 minutes to 60 minutes under the condition of temperature of 130° C. to 150° C. to obtain a durable super-hydrophilic coating for a flexible substrate.
[0015] The beneficial effects of the present invention are:
[0016] The present invention uses a copolyester aqueous emulsion containing hydroxyl and carboxyl side groups, an aqueous resin system curing agent, isopropyl alcohol, and nano barium sulfate to prepare a durable super hydrophilic coating for a flexible substrate. The aqueous resin system curing agent is a melamine resin curing agent, a blocked isocyanate curing agent, or a polyamine epoxy curing agent. Isopropyl alcohol is used as a defoamer and a leveling agent, and the surface tension of the aqueous emulsion and the spreadability on the substrate are adjusted by adjusting the amount of isopropyl alcohol. The present invention can prepare a transparent hydrophilic coating suitable for a variety of substrates, such as tinplate sheets, stainless steel substrates, silicate glass, PET films, etc., and has excellent adhesion and flexibility, and is particularly suitable for flexible substrates such as PET films. In addition, the coating has excellent durability and can still maintain excellent hydrophilicity under a variety of use environments and aging conditions.
[0017] Compared with the three types of hydrophilic coating preparation schemes reported in the literature, such as silicon dioxide coating, titanium dioxide coating and traditional organic polymer hydrophilic coating, the preparation process of the present invention is simple, and the prepared hydrophilic coating has excellent flexibility and adhesion. By adjusting the ratio of the copolyester aqueous emulsion, the curing agent and isopropanol, the surface tension is used to regulate the assembly structure of the emulsion particles and then regulate the surface roughness of the coating. Excellent hydrophilicity can be achieved without adding additional hydrophilic additives and fillers, and no ultraviolet light is required, and the defects of the existing organic polymer hydrophilic coating such as poor resistance to wiping, swelling in water, and poor wear resistance are avoided. By adding one of the melamine resin curing agent, the blocked isocyanate curing agent and the polyamine epoxy curing agent, the cross-linking of the copolyester molecular chain in the emulsion is achieved, thereby improving the durability and stability of the hydrophilic coating, and avoiding the defects of the general organic polymer hydrophilic coating such as poor resistance to wiping, swelling in water, and poor wear resistance. Corona treatment generates high-voltage corona discharge on the surface of the initially formed coating, forming low-temperature plasma, which causes free radical reaction on the coating surface, making the surface rough and increasing its wettability to polar liquids. These plasmas enter the treated surface by electric shock and penetration, destroying its molecular structure, and then oxidizing and polarizing the treated surface molecules, increasing the surface energy, and increasing the adhesion ability of the coating surface.
[0018] Unexpectedly, the super-hydrophilic coating prepared by the present invention not only exhibits excellent hydrophilicity, light transmittance and flexibility, but also exhibits anti-reflection and anti-transmittance performance. When coated on transparent substrates such as glass and PET film, it exhibits higher light transmittance. This may be because the coating has a refractive index between air and substrate, forming a three-layer optical medium of air-coating-substrate, and using the optical path difference of the reflected light on the upper and lower surfaces of the coating to meet the destructive interference condition to reduce reflection, thereby enhancing transmission. The introduction of nano-barium sulfate improves the surface roughness of the coating while improving friction resistance and durability, and further improves the hydrophilicity of the coating based on the Wenzel equation. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Infrared spectra of the durable super-hydrophilic coatings prepared in Examples 1 and 2, (A) Example 1, (B) Example 2;
[0020] Figure 2 Surface roughness (Ra) diagram of the durable super hydrophilic coating prepared in Example 2, Example 5, Example 6 and Example 7, (A) Example 2, (B) Example 5, (C) Example 6, (D) Example 7;
[0021] Figure 3The light transmittance comparison diagram of the durable super hydrophilic coating prepared for the glass slide, Example 1, Example 2, Example 5 and Example 10, (A) Example 1, (B) Example 2, (C) Example 5, (D) Example 10;
[0022] Figure 4 The water contact angle test diagrams of the durable super hydrophilic coatings prepared in Examples 1 and 2, (A) Example 1, (B) Example 2;
[0023] Figure 5 The light transmittance comparison diagram of the durable super hydrophilic coatings prepared in Example 1, Example 2, Example 5 and Example 10 after thermal aging, (A) Example 1, (B) Example 2, (C) Example 5, (D) Example 10;
[0024] Figure 6 This is a test chart of adhesion and flexibility of the PET film covered with a durable super-hydrophilic coating prepared in Example 2. DETAILED DESCRIPTION
[0025] Specific implementation method 1: This implementation method is a durable super hydrophilic coating for a flexible substrate, which is prepared by 100 parts by mass of an aqueous copolyester emulsion containing hydroxyl and carboxyl side groups, 2 to 35 parts of an aqueous resin system curing agent, 5 to 30 parts of isopropanol and 2 to 5 parts of nano barium sulfate.
[0026] The beneficial effects of this embodiment are:
[0027] This embodiment uses a copolyester aqueous emulsion containing hydroxyl and carboxyl side groups, an aqueous resin system curing agent, isopropanol, and nano barium sulfate to prepare a durable super hydrophilic coating for a flexible substrate. The aqueous resin system curing agent is a melamine resin curing agent, a blocked isocyanate curing agent, or a polyamine epoxy curing agent. Isopropanol is used as a defoamer and leveling agent, and the surface tension of the aqueous emulsion and its spreadability on the substrate are adjusted by adjusting the amount of isopropanol. This embodiment can prepare a transparent hydrophilic coating suitable for a variety of substrates, such as tinplate, stainless steel substrate, silicate glass, PET film, etc., and has excellent adhesion and flexibility, and is particularly suitable for flexible substrates such as PET film. In addition, the coating has excellent durability and can still maintain excellent hydrophilicity under a variety of use environments and aging conditions.
[0028] Compared with the three types of hydrophilic coating preparation schemes reported in the literature, such as silicon dioxide coating, titanium dioxide coating and traditional organic polymer hydrophilic coating, the preparation process of this embodiment is simple, and the prepared hydrophilic coating has excellent flexibility and adhesion. By adjusting the ratio of copolyester aqueous emulsion, curing agent and isopropanol, the surface tension is used to regulate the assembly structure of emulsion particles and then regulate the surface roughness of the coating. Excellent hydrophilicity can be achieved without adding additional hydrophilic additives and fillers, and no ultraviolet light is required, and the defects of existing organic polymer hydrophilic coatings such as poor resistance to wiping, swelling in water, and poor wear resistance are avoided. By adding one of melamine resin curing agent, blocked isocyanate curing agent and polyamine epoxy curing agent, the cross-linking of copolyester molecular chains in the emulsion is achieved, thereby improving the durability and stability of the hydrophilic coating, avoiding the defects of general organic polymer hydrophilic coatings such as poor resistance to wiping, swelling in water, and poor wear resistance. Corona treatment generates high-voltage corona discharge on the surface of the initially formed coating, forming low-temperature plasma, which causes free radical reaction on the coating surface, making the surface rough and increasing its wettability to polar liquids. These plasmas enter the treated surface by electric shock and penetration, destroying its molecular structure, and then oxidizing and polarizing the treated surface molecules, increasing the surface energy, and increasing the adhesion ability of the coating surface.
[0029] Unexpectedly, the super-hydrophilic coating prepared in this embodiment not only exhibits excellent hydrophilicity, light transmittance and flexibility, but also exhibits anti-reflection and anti-transmittance performance. When coated on transparent substrates such as glass and PET film, it exhibits higher light transmittance. This may be because the coating has a refractive index between air and substrate, forming a three-layer optical medium of air-coating-substrate, and using the optical path difference of the reflected light on the upper and lower surfaces of the coating to meet the destructive interference condition to reduce reflection, thereby enhancing transmission. The introduction of nano-barium sulfate improves the surface roughness of the coating while improving friction resistance and durability, and further improves the hydrophilicity of the coating based on the Wenzel equation.
[0030] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the solid content of the aqueous copolyester emulsion containing hydroxyl and carboxyl side groups is 20 wt% to 40 wt%. Other aspects are the same as those of specific embodiment 1.
[0031] The aqueous copolyester emulsion containing hydroxyl and carboxyl side groups described in this specific embodiment can be Toyobo MD-1100, MD-1400 or MD-1480, Korean SK Chemical EW100Q or EW 210.
[0032] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the water-based resin system curing agent is a melamine resin curing agent, a blocked isocyanate curing agent or a polyamine epoxy curing agent. The rest is the same as specific implementation method 1 or 2.
[0033] The melamine resin curing agent described in this specific embodiment can be CYMEL303LF amino resin or CYMEL 325 amino resin; the blocked isocyanate curing agent described in this specific embodiment can be a water-based isocyanate curing agent XP 2655; the polyamine epoxy curing agent described in this specific embodiment may be CYDHD-220.
[0034] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that the particle size of the nano barium sulfate is 30nm to 100nm. The rest is the same as specific embodiments 1 to 3.
[0035] Specific embodiment 5: This embodiment is a method for preparing a durable super-hydrophilic coating for a flexible substrate, which is carried out according to the following steps:
[0036] 1. Preparation of aqueous emulsion:
[0037] Weigh 100 parts by mass of an aqueous copolyester emulsion containing hydroxyl and carboxyl side groups, 2 to 35 parts by mass of an aqueous resin system curing agent, 5 to 30 parts by mass of isopropanol and 2 to 5 parts by mass of nano-barium sulfate, and then stir at high speed until the mixture is uniformly mixed to obtain an aqueous emulsion;
[0038] 2. Coating:
[0039] The aqueous emulsion is coated on a substrate at a temperature of 40°C to 80°C, and finally dried to obtain a coating layer;
[0040] 3. Electrostatic treatment:
[0041] Performing electrostatic surface treatment on the coating layer by using a corona roller to obtain an electrostatically treated coating;
[0042] 4. Curing treatment:
[0043] The coating after electrostatic treatment is cured for 20 minutes to 60 minutes under the condition of temperature of 130° C. to 150° C. to obtain a durable super-hydrophilic coating for a flexible substrate.
[0044] Specific implementation example 6: This implementation example is different from specific implementation example 5 in that the high-speed stirring in step 1 is performed at a rotation speed of 1000 r / min to 5000 r / min for 2 to 6 hours. The rest is the same as specific implementation example 5.
[0045] Specific embodiment 7: This embodiment is different from specific embodiment 5 or 6 in that the substrate described in step 2 is a tinplate sheet, a stainless steel substrate, a silicate glass or a PET film. The rest is the same as specific embodiment 5 or 6.
[0046] Specific embodiment 8: This embodiment is different from specific embodiments 5 to 7 in that the drying described in step 2 is carried out at a temperature of 40° C. to 80° C. for 10 to 20 minutes. The rest is the same as specific embodiments 5 to 7.
[0047] Specific embodiment 9: This embodiment is different from specific embodiments 5 to 8 in that the thickness of the coating layer in step 2 is 5 micrometers to 150 micrometers. Other aspects are the same as specific embodiments 5 to 8.
[0048] Specific embodiment 10: This embodiment differs from specific embodiments 5 to 9 in that in step 3, the coating layer is subjected to electrostatic surface treatment using a corona roller at a voltage of 5000V to 10000V and a corona roller speed of 1m / min to 10m / min. The rest is the same as specific embodiments 5 to 9.
[0049] The following examples are used to verify the beneficial effects of the present invention:
[0050] Embodiment 1:
[0051] A method for preparing a durable super-hydrophilic coating for a flexible substrate is carried out according to the following steps:
[0052] 1. Preparation of aqueous emulsion:
[0053] Weigh 100 parts by mass of an aqueous copolyester emulsion containing hydroxyl and carboxyl side groups, 5 parts of an aqueous resin system curing agent, 5 parts of isopropanol and 3 parts of nano-barium sulfate, and then stir at a speed of 2000 r / min for 2 hours to obtain an aqueous emulsion;
[0054] The solid content of the aqueous copolyester emulsion containing hydroxyl and carboxyl side groups is 30wt%; the aqueous copolyester emulsion containing hydroxyl and carboxyl side groups is Toyobo MD-1100;
[0055] The water-based resin system curing agent is XP 2655;
[0056] The average particle size of the nano barium sulfate is 50 nm;
[0057] 2. Coating:
[0058] The aqueous emulsion is coated on a substrate at a temperature of 60°C, and finally dried at a temperature of 60°C for 20 minutes to obtain a coating layer;
[0059] The substrate is a tinplate sheet, a glass slide or a PET film; the thickness of the coating layer is 100 microns;
[0060] 3. Electrostatic treatment:
[0061] At a voltage of 5000V / m 2 Under the condition that the rotation speed of the corona roller is 5 m / min, the coating layer is subjected to electrostatic surface treatment by using a corona roller to obtain an electrostatically treated coating;
[0062] 4. Curing treatment:
[0063] The electrostatically treated coating was cured at a temperature of 130° C. for 30 min to obtain a durable super hydrophilic coating.
[0064] The difference between Examples 2 to 10 and Example 1 is that the combined content of the aqueous emulsion in step 1 is changed, as shown in Table 1. The rest is the same as Example 1.
[0065] Table 1
[0066]
[0067] The test conditions are carried out according to the following standards or methods:
[0068] 1. Infrared spectrum analysis:
[0069] In step 2, the aqueous emulsion is coated on the tinplate sheet and the sample is analyzed by Fourier transform infrared spectrometer (FTIR, Nicolet iS5) at 500 cm -1 ~4000cm -1 The characteristic absorption peaks of the hydrophilic coating groups were analyzed within the range of .
[0070] 2. Coating roughness test:
[0071] In step 2, the aqueous emulsion is coated on the tinplate sheet, and the surface roughness (Ra) of the prepared coating is measured by a Taylor Hobson roughness measuring instrument Surtronic S-128.
[0072] 3. Coating transmittance:
[0073] In step 2, the aqueous emulsion is coated on a glass slide, and the light transmittance of the coating is measured using a fiber optic spectrometer (Maya 2000PRO, Ocean Optics).
[0074] 4. Wear resistance of coating:
[0075] In step 2, the aqueous emulsion is coated on the tinplate sheet, and the wear resistance of the coating is tested using Rtec MFT5000. The friction force is set to 10N using a silicon nitride wear head for 180 seconds (120Hz / min). The friction resistance of the coating is evaluated by the weight loss ratio after the test.
[0076] 5. Coating hydrophilicity test:
[0077] In step 2, the aqueous emulsion is coated on the tinplate sheet, and a proper amount of deionized water is added to the coating surface to allow the deionized water to spread naturally. Then, a photo is taken and the contact angle of the coating surface is measured by the goniometer method.
[0078] 6. Impact strength of coating:
[0079] In step 2, the aqueous emulsion is coated on the tinplate sheet, and the impact strength of the coating is tested according to GB / T1732-1993.
[0080] 7. Pencil hardness test:
[0081] In step 2, the water-based emulsion is coated on the tinplate sheet, and the hardness of the coating is tested according to GB / T6739-2006 "Paints and varnishes - Determination of film hardness by pencil method".
[0082] 8. Bendability test:
[0083] In step 2, the water-based emulsion is coated on the tinplate sheet. The bending resistance of the coating reflects the flexibility and adhesion of the coating. According to the GB / T 6742-2007 paint and varnish bending test (cylindrical shaft) standard, the coating (specification: 120mm×50mm×0.3mm) is tested: the paint film cone bending tester shaft rod with a diameter of 12, 10, 8, 6, 4, and 2mm is rotated from large to small, and the minimum diameter of the shaft without damage to the coating when bent is recorded. The diameter number is the bending value of the coating at this time.
[0084] 9. Adhesion test:
[0085] In step 2, the water-based emulsion is coated on the tinplate sheet. Adhesion indicates the strength of the bonding between the coating and the base material. According to the evaluation requirements of the GBT9286-1998 cross-cut test for paints and varnishes, the adhesion of the coating is tested. A cross-cut tool is used to cross-cut the coating surface at a uniform speed, and each small grid is 2mm×2mm. A transparent tape is attached to the coating surface and left for 1 minute, and the tape is quickly torn off.
[0086] 10. Coating stability test:
[0087] High temperature stability: The coating was placed in a high temperature ventilation oven at 140°C for 8 hours of heat aging.
[0088] Water resistance: Place the coating in a beaker filled with an appropriate amount of pure water (make sure the iron sheet is completely immersed) for 24 hours and seal the beaker mouth.
[0089] Anti-ultraviolet aging: Place the coating under ultraviolet light (power 40w, intensity = 1mW / cm 2 ) for 24 hours, and the distance from the UV lamp to the coating was fixed at 5 cm.
[0090] After treatment, the coatings were tested for light transmittance, abrasion resistance, hydrophilicity, impact resistance, pencil hardness, bendability and adhesion.
[0091] Figure 1 The infrared spectra of the durable super-hydrophilic coatings prepared in Example 1 and Example 2, (A) Example 1, (B) Example 2; As can be seen from the figure, 1652cm -1 The characteristic absorption peak of amide bond is at 2930cm, which proves that the reaction between isocyanate curing agent and copolyester molecular chain occurs to generate amide bond which is not originally present in copolyester. -1 With 2880cm -1 The stretching vibration absorption peak of CH2 is 1720cm -1 The carbonyl C=O stretching vibration absorption peak is 1105cm -1 and 1250cm -1 The stretching vibration absorption peak of the ether bond COC is shown at 700~900cm. The combination of carbonyl and ether bond is an ester group, which proves the ester structure in the copolyester. -1 The range is also called the benzene ring substitution region. The peak in this region proves the existence of the benzene ring at 729 cm -1 The stretching vibration absorption peak at is due to the out-of-plane bending of the CH on the para-substituted benzene ring.
[0092] Figure 2The surface roughness (Ra) diagram of the durable super hydrophilic coating prepared in Example 2, Example 5, Example 6 and Example 7, (A) Example 2, (B) Example 5, (C) Example 6, (D) Example 7; As can be seen from the figure, the surface roughness (Ra) of the coating prepared in Example 2, Example 5, Example 6 and Example 7 is 0.1016μm, 0.0683μm, 0.0517μm and 0.0377μm respectively, and the surface roughness (Ra) of the coating decreases with the increase of the amount of isopropanol added. This is because the addition of isopropanol reduces the surface tension of the emulsion. In the process of coating drying and molding, the low surface tension is conducive to the smooth accumulation of emulsion particles, thereby reducing the surface roughness of the coating. Therefore, a lower amount of isopropanol added can appropriately increase the surface tension of the emulsion during coating and molding, and the self-assembly accumulation of emulsion particles based on surface tension improves the surface roughness of the coating, and according to the Wenzel equation, the hydrophilicity of the coating can be effectively improved.
[0093] Figure 3 The transmittance comparison chart of the durable super hydrophilic coating prepared for the glass slide, Example 1, Example 2, Example 5 and Example 10, (A) Example 1, (B) Example 2, (C) Example 5, (D) Example 10; it can be seen from the figure that compared with the glass slide substrate, the coating improves the transmittance of the sample and plays a role in increasing transmittance and reducing reflection. The durable super hydrophilic coating prepared in Example 1, Example 2 and Example 5 has a transmittance greater than 95% in the visible light range.
[0094] Table 2 Performance of durable superhydrophilic coatings
[0095]
[0096]
[0097] In the table, the coating bendability test of level 1 means that the coating is not damaged or falls off when tested with a 2mm diameter shaft. The adhesion test of level 0 means that the cutting edge is completely smooth without any falling off.
[0098] Figure 4 The water contact angle test diagrams of the durable super hydrophilic coatings prepared in Examples 1 and 2, (A) Example 1, (B) Example 2;
[0099] The coating properties are shown in Table 2. The hydrophilic coatings prepared in each embodiment show excellent light transmittance, and can achieve a light transmittance of up to 97.9%. They also show excellent hydrophilic properties, especially the coatings prepared in Embodiments 5 and 10 are super hydrophilic coatings. In addition, the coatings also have excellent basic properties, such as impact resistance, pencil hardness test, coating flexibility, adhesion, etc.
[0100] Table 3 Properties of durable superhydrophilic coatings after thermal aging
[0101]
[0102]
[0103] In the table, the coating bendability test of level 1 means that the coating is not damaged or falls off when tested with a 2mm diameter shaft. The adhesion test of level 0 means that the cutting edge is completely smooth without any falling off.
[0104] Figure 5 The light transmittance comparison diagram of the durable super hydrophilic coatings prepared in Example 1, Example 2, Example 5 and Example 10 after thermal aging, (A) Example 1, (B) Example 2, (C) Example 5, (D) Example 10;
[0105] The coating properties after thermal aging test are shown in Table 3. After thermal aging, the light transmittance of the coating decreased, but it was still higher than 86%, with good light transmittance. After thermal aging, the coating still maintained excellent hydrophilicity.
[0106] Table 4 Performance of durable superhydrophilic coating after water resistance
[0107]
[0108] In the table, the coating bendability test of level 1 means that the coating is not damaged or falls off when tested with a 2mm diameter shaft. The adhesion test of level 0 means that the cutting edge is completely smooth without any falling off.
[0109] The coating properties after water resistance test are shown in Table 4. After immersion in pure water for 24 hours, the pencil hardness of the coating decreased, but it still maintained excellent impact resistance, flexibility and adhesion.
[0110] Table 5 Durable super hydrophilic coating performance after UV test
[0111]
[0112] In the table, the coating bendability test of level 1 means that the coating is not damaged or falls off when tested with a 2mm diameter shaft. The adhesion test of level 0 means that the cutting edge is completely smooth without any falling off.
[0113] The coating properties after UV testing are shown in Table 5. Compared with thermal aging, the performance of the coating after UV aging does not decrease significantly, and the coating exhibits excellent anti-UV aging performance.
[0114] The aqueous emulsion prepared in Example 2 was coated on a PET film to test the adhesion and flexibility of the coating on the flexible substrate. Figure 6 shown. Figure 6 This is a test chart of the adhesion and flexibility of the PET film covered with a durable super hydrophilic coating prepared in Example 2; as can be seen from the figure, after being folded 180° and unfolded, there is no damage such as cracking, whitening or falling off, showing excellent adhesion and flexibility.
Claims
1. A durable super-hydrophilic coating for a flexible substrate, characterized in that The invention is prepared from 100 parts by mass of an aqueous copolyester emulsion containing hydroxyl and carboxyl side groups, 2 to 35 parts by mass of an aqueous resin system curing agent, 5 to 30 parts by mass of isopropanol and 2 to 5 parts by mass of nano-barium sulfate.
2. A durable super hydrophilic coating for a flexible substrate according to claim 1, characterized in that The solid content of the aqueous copolyester emulsion containing hydroxyl and carboxyl side groups is 20wt% to 40wt%.
3. A durable super hydrophilic coating for a flexible substrate according to claim 1, characterized in that The water-based resin system curing agent is a melamine resin curing agent, a blocked isocyanate curing agent or a polyamine epoxy curing agent.
4. A durable super hydrophilic coating for a flexible substrate according to claim 1, characterized in that The particle size of the nano barium sulfate is 30nm-100nm.
5. The method for preparing a durable super hydrophilic coating for a flexible substrate as claimed in claim 1, characterized in that It is carried out in the following steps:
1. Preparation of aqueous emulsion: Weigh 100 parts by mass of an aqueous copolyester emulsion containing hydroxyl and carboxyl side groups, 2 to 35 parts by mass of an aqueous resin system curing agent, 5 to 30 parts by mass of isopropanol and 2 to 5 parts by mass of nano-barium sulfate, and then stir at high speed until the mixture is uniformly mixed to obtain an aqueous emulsion; 2. Coating: The aqueous emulsion is coated on a substrate at a temperature of 40°C to 80°C, and finally dried to obtain a coating layer; 3. Electrostatic treatment: Performing electrostatic surface treatment on the coating layer by using a corona roller to obtain an electrostatically treated coating; 4. Curing treatment: The coating after electrostatic treatment is cured for 20 minutes to 60 minutes under the condition of temperature of 130° C. to 150° C. to obtain a durable super-hydrophilic coating for a flexible substrate.
6. The method for preparing a durable super-hydrophilic coating for a flexible substrate according to claim 5, characterized in that The high-speed stirring described in step 1 specifically involves stirring for 2h to 6h at a rotation speed of 1000r / min to 5000r / min.
7. The method for preparing a durable super-hydrophilic coating for a flexible substrate according to claim 5, characterized in that The substrate described in step 2 is a tinplate sheet, a stainless steel substrate, a silicate glass or a PET film.
8. The method for preparing a durable super-hydrophilic coating for a flexible substrate according to claim 5, characterized in that The drying described in step 2 is specifically carried out at a temperature of 40° C. to 80° C. for 10 min to 20 min.
9. The method for preparing a durable super-hydrophilic coating for a flexible substrate according to claim 5, characterized in that The thickness of the coating layer in step 2 is 5 micrometers to 150 micrometers.
10. The method for preparing a durable super-hydrophilic coating for a flexible substrate according to claim 5, characterized in that In step three, the coating layer is subjected to electrostatic surface treatment using a corona roller at a voltage of 5000V to 10000V and a corona roller speed of 1m / min to 10m / min.
Citation Information
Patent Citations
Polyester type water-borne emulsion, preparing method and application thereof
CN106318145A
Waterborne resin antifogging coating special for films and antifogging film
CN108084853A
Retroreflective articles including cured ceramer composite coating having abrasion and stain resistant characteristics
CN1307660A